ANTIINFLAMMATORY EFFECTS OF FRACTION FROM GALING STEM ETHANOL EXTRACT (Cayratia trifolia L. Domin) IN VITRO - Muhammad Ilyas Y; Muhammad Syaiful Saehu; Ertin Ertin; Irma Irma; Nurhikma Nurhikma (Jurnal Farmasi Sains dan Praktis, 2021)
Galing plant (Cayratia trifolia L. Domin) is a wild plant that spreads and is easily found in Indonesia, especially in the lowlands, which contains a class of secondary metabolites such as flavonoids, polyphenols, alkaloids, terpenoids, and triterpenoids with various pharmacological activities such as antidiabetic, immunomodulatory, antibacterial, anti-fungal, anti-diarrhea, gout. This study aims to determine the antiinflammatory effect of several fractions of rod galing using the in vitro model of red blood cell membrane stabilization. This study used an ethanol extract fractionated in a liquid-liquid manner with n-hexane, ethyl acetate, and water as a solvent. Then, the anti-inflammatory effect of each fraction was tested, with a positive control comparison of diclofenac sodium with varying concentrations. Measurement of anti-inflammatory activity was calculated based on the % stability of the red blood cell membrane. The results showed that the ethyl acetate, n-hexane and water fractions from the ethanol extract of galing (Cayratia trifolia L. Domin.) stem had an anti-inflammatory effect based on the % stability of red blood cell membranes, where the ethyl acetate fraction with a concentration of 1000 ppm had the best anti-inflammatory effect with % stability of red blood cell membranes was 91.81%, which was significantly different from the positive control (p<0.05).